Reflections on Working Together in an Inclusive Research Team - Phillippa Carnemolla; Jack Kelly; Catherine Donnelley; Aine Healy (Social Sciences, 2022)
The funding of a research project working with local governments and people with intellectual disabilities led to the establishment of an inclusive research team within a university faculty. The core team consisted of four people, including a design researcher, an architect, a disability advocate and a community researcher/self-advocate. Though there are ample attention and resources devoted to the front-facing parts of a university being visibly inclusive—mostly from a physical access perspective or focussed on the student experience—less attention has been directed to what it means to develop and support inclusive research and aligned work opportunities for people with intellectual disabilities within a university campus. For this reason, the paper explores what it was like for our team that included non-traditional academics and people with intellectual disabilities to work at a university in a design school (not a disability-related research centre). We employ a process of collaborative autoethnography to reflect on how different team members took the lead across different parts of the study. We conclude with a set of tips for the development of more inclusive research teams within university settings.